Manhunt - Felker-Martin, Gretchen (Nightfire, 2022)
"Beth and Fran spend their days traveling the ravaged New England coast, hunting feral men and harvesting their organs in a gruesome effort to ensure they'll never face the same fate. Robbie lives by his gun and one hard-learned motto: other people aren't safe. After a brutal accident entwines the three of them, this found family of survivors must navigate murderous TERFs, a sociopathic billionaire bunker brat, and awkward relationship dynamics--all while outrunning packs of feral men, and their own demons."--